Silver release from dentine treated with combinations of silver diamine fluoride, potassium iodide and etching. Issue 1 (31st December 2023) - Staxrud, Frode; Becher, Rune; Syverud, Morten; Azulay, Naomi; Valen, Håkon
Abstract: For individuals with very high to extremely high caries activity and poor control of daily oral hygiene, a simple treatment for arresting their caries activity is necessary. Silver Diamine Fluoride (SDF) has become increasingly common for this purpose due to its efficacy and ease of application. To avoid or reduce tooth discoloration after SDF treatment potassium iodide (KI) may be applied. However, the release of silver from SDF-treated tooth surfaces may be of concern. Thus, the aim of the present study was to quantify the amount of silver leached in both a short- and long-term perspective. In this in vitro experiment we measured the cumulative release of silver from SDF-treated dentin surfaces with and without imminent application of KI, and with and without phosphoric acid etching as pre-treatment, after 24 h and weekly for four weeks. The release of silver was highest after 24 h for all treatment groups, with a significant drop after this point. When etching was not used, the use of KI did not affect the release of silver. However, when etching was used, there was a significantly lower silver release when KI was also used compared to when KI was not used. This effect was largest for the first two weeks, after which the difference was smaller as all groups released low amounts of silver.